2020
DOI: 10.1007/978-3-030-58653-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Functional Control for Unstable First-Order Dynamic Systems

Abstract: Predictive functional control (PFC) has emerged as a popular industrial choice owing to its simplicity and cost-effectiveness. Nevertheless, its efficacy diminishes when dealing with challenging dynamics because of prediction mismatch in such scenarios. This paper presents a proposal for reducing prediction mismatch and thus improving behaviour for simple unstable processes; a two-stage design methodology pre-stabilises predictions via proportional compensation before introducing the PFC component. It is demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The most recent suggestion for modifying PFC builds on some ideas with the case by case modifications for the original algorithm [6] but implements this in a more systematic and effective manner. The basic idea is to recognise that where a system has poor openloop dynamics, a simple feedback loop, often based solely on simple proportional control, can improve those dynamics [11,16,17]. As the efficacy of PFC is strongly linked to the nominal dynamics having a shape somewhat close to a well-damped system, this initial prestabilisation can be hugely effective in enabling PFC.…”
Section: Closed-loop or Pre-stabilised Pfcmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent suggestion for modifying PFC builds on some ideas with the case by case modifications for the original algorithm [6] but implements this in a more systematic and effective manner. The basic idea is to recognise that where a system has poor openloop dynamics, a simple feedback loop, often based solely on simple proportional control, can improve those dynamics [11,16,17]. As the efficacy of PFC is strongly linked to the nominal dynamics having a shape somewhat close to a well-damped system, this initial prestabilisation can be hugely effective in enabling PFC.…”
Section: Closed-loop or Pre-stabilised Pfcmentioning
confidence: 99%
“…• CLPFC clearly demonstrates a much stronger link between the actual and the desired closed-loop performance, even with longer coincidence horizons. This is important since long horizons may be necessary for better loop shaping against external perturbations, as pointed out in [17]. Furthermore, the control effort with CLPFC is smooth and the least aggressive as opposed to both CPFC and LPFC, which is crucial for constraint adherence in practice.…”
Section: Tuning Efficacy and Closed-loop Performance Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as highlighted in the recent review paper [1], simplicity and computational efficiency come at a cost, that is, the tuning of PFC is often not as straightforward or effective as one would like [12]; thus, recent research efforts, such as the development of closed-loop PFC [13,14], Laguerre PFC [15], PFC with an improved feedforward component [16], and designs based on model decomposition [17,18], have focussed improving tuning efficacy. This paper will not repeat the review of those methods (see [1] for details), but will rather develop and extend them.…”
Section: Introductionmentioning
confidence: 99%
“…All of the recently developed proposals have used the same defining principle and have focussed on how the input degrees of freedom are parameterised; changing the input predictions has a significant impact on the efficacy of the overall design.Indeed, this latter point will be preserved in the proposal of this paper, as it is well known in the MPC field [20,21] that consistency between open-loop predictions and closed-loop behaviour is a solid foundation for sensible MPC design. Recent work has shown that there are two input parameterisations that, in general, seem to be more effective in ensuring this consistency: (i) Laguerre-based parameterisations [15] and (ii) parameterisations that exploit an inner feedback loop [13,14,22]. Consequently, this paper will mainly focus on those two input parameterisations.…”
Section: Introductionmentioning
confidence: 99%